The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.12693/aphyspola.125.426
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Synthesis of Free-Standing ZnO/MWCNT Nanocomposites by Vacuum Infiltration

Abstract: In this study, free-standing zincoxide/multiwalled carbon nanotube nanocomposite was synthesized by a multistep technique. Buckypapers having controlled porosity were prepared by vacuum ltration from oxidized multiwalled carbon nanotubes. Zinc acetate dihydrate (ZnAc) (Zn(CH3COO)2·2H2O) was used as zinc source and ethanol used as solvent. An appropriate amount of monoethanolamine was added to sol to change acid-base media. The solution was vacuum ltered through buckypaper and annealed at 350• C in air. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…In literature, very few studies of free-standing ZnO films were applied for using different purposes such as anode application [4,34,35]. Akbulut et al synthesized ZnO/MWCNT nanocomposites by coating active materials on the filtration produced MWCNT buckypapers.…”
Section: Resultsmentioning
confidence: 99%
“…In literature, very few studies of free-standing ZnO films were applied for using different purposes such as anode application [4,34,35]. Akbulut et al synthesized ZnO/MWCNT nanocomposites by coating active materials on the filtration produced MWCNT buckypapers.…”
Section: Resultsmentioning
confidence: 99%
“…23 Up to know, various methods, such as chemical vapour deposition (CVD), plasma assisted sputter and vacuum infiltration, have been carried out to modify the surface of MWCNT with ZnO nanoparticles. [24][25][26] Koh et al also reported the coating of ZnO nanorods on MWCNT using hydrothermal synthesis. 27 CNTs decorated with ZnO nanoparticles were synthesized by Chen et al through oxidization, amination and modification of MWCNT with H 2 SO 4 , NH 3 and HNO 3 .…”
Section: Introductionmentioning
confidence: 99%